The Women’s Prize for Fiction and Book Studies - Rosenberg, Simon (Satura, 2018)
In 2005, the controversial novel We Need to Talk About Kevin by Lionel Shriver was published. It caused a major dispute, especially in the United States of America, since it addressed the sensitive issue of school shootings. Also shattering the last taboo of motherhood, as the British Telegraph put it, the novel tells the story of a mother who does not connect emotionally with her son and blames him for her failed career and marriage (“Controversial”). Although provocative in itself, it was the book’s winning the “Women’s Prize for Fiction” (WPfF) which acted as a catalyst for the controversy. Not only did the novel now reach a bigger audience, but the prize obviously rewarded authors writing about shocking topics. Awarded to women writers since 1996, the prize had already been controversial for years at the time of Shriver’s win and once again proved to spark gender debates. Book Studies seems to be a good point of departure to discuss the WPfF and its controversies in an academic way. This discipline, once famously described as “interdisciplinarity run riot” (Darnton 67) nowadays engages in the production, distribution and reception of books, as well as with all possible influences, be they economic, political, sociocultural, religious or otherwise.